Underwater Imaging Sustainable Underwater Expedition to Taman Laut Pulau Payar, Kedah Darulaman - Aslina, Mohd Jainal; Anuar, Ayob (UNIMAS Publisher, 2024)
Students of GKF2134 Underwater Imaging were immersed in the fascinating world of underwater imaging during their field trip from May 2nd to 10th, 2024. Led by the experienced guidance of Mr. Fuad Osman and his awesome team from the Nudi Dive Centre affiliated with the National Association of Underwater Instructors (NAUI), this expedition to Taman Laut Pulau Payar, Kedah, left a significant mark on the 20 students. Over the 9 days, 16 students achieved certification as Open Water SCUBA Divers, while 4 advanced their skills to the level of Advanced Open Water Divers. The itinerary wasn't just about certification. It was a holistic exploration of marine conservation and creativity. Students engaged in captivating photo and videography sessions, capturing the vibrant marine life that grows well beneath the surface. Moreover, they contributed to coral restoration efforts alongside the dedicated staff of Taman Laut, Mr. Hatim bin Ramizon (Pembantu Laut, Jabatan Perikanan Negeri Kedah), recognizing the importance of conserving and protecting our oceans and their habitats. As they returned to shore, each participant carried with them not only newfound certifications and captured the ocean's secrets but also a deeper understanding of the beauty and fragility of our underwater ecosystems.